APOLOGIJA NEPOSLUŠNOSTI IN POČASNOSTI V ROMANU AZBUKA ZA NEPOSLUŠNE VENKA ANDONOVSKEGA (Filološke pripombe, 2019)
In most of his prose works Venko Andonovski creates contrast, a kind of Manichean dualism, from which rise issues on the ethics and morality of human practices and manners, and the change, perhaps decadence of values in the new (present) times. In the novel Alphabet for the Disobedients (1993), considered in this paper, this is particularly visible. The author discusses the speed in this novel, which raises the sloppiness and mistakes, and favors slowness, which protects the beauty and the truth. By doing so, it seems that he is approaching the defenders of the apocalyptic vision of the world, according to Eco’s division of intellectuals in the apocalyptic and the integrated. At the core of their criticism is acceleration and speed, which transform one into insensitive human being, that’s why they appreciate the ancient slowness. Andonovski derives from this idea, by beaming the acceleration/speed that he senses in the early nineties into the second half of the "slow" ninth century, which is the narrative time of the novel. He marks the advocates of slowness as "disobedient".
Keywords: Macedonian literature, Novel, Venko Andonovski, Slowness